(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The National Bank for Agriculture and Rural Development (NABARD) has been instrumental in promoting agricultural development in India, particularly in rural regions. This research paper focuses on the various schemes implemented by NABARD in Chandrapur District, Maharashtra, highlighting their objectives, methodologies, and impacts on local agriculture. By utilizing qualitative and quantitative research methodologies, interviews with stakeholders. This study assesses the effectiveness of NABARD’s initiatives in enhancing agricultural productivity and improving rural livelihoods. The findings reveal significant advancements in irrigation, credit access, and community empowerment, while also identifying challenges that need to be addressed for sustainable development.